2014
DOI: 10.15345/iojes.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Examination of High School Students’ Learned Resourcefulness: A Review of Gender, Parental Attitudes, and Values

Abstract: High school education is a process involving quite challenging life situations such as university entrance exam preparation, career choice, as well as autonomy development. While some students overcome with the difficulties successfully, the others might not demonstrate the same skills. The differences among students are explained with learned resourcefulness. Many factors such as the relationships with parents have an effect to develop learned resourcefulness. In this study, determination of the predictive po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…There are various researches in literature about the effect of gender on learned resourcefulness. Within the context of gender, different findings were obtained in the studies carried out in our country (Erden S.& Ümmet D. (2014) In other research, the findings revealed that in general, the students' self-acceptance level increased in the four-year period that included university education. With respect to gender, the self acceptance level of female students was found to increase during their university education, while no difference was observed in that of male students.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…There are various researches in literature about the effect of gender on learned resourcefulness. Within the context of gender, different findings were obtained in the studies carried out in our country (Erden S.& Ümmet D. (2014) In other research, the findings revealed that in general, the students' self-acceptance level increased in the four-year period that included university education. With respect to gender, the self acceptance level of female students was found to increase during their university education, while no difference was observed in that of male students.…”
Section: Discussionmentioning
confidence: 66%
“…According to Rosenbaum, the skills under the learned resourcefulness are learned through informal ways from an early age and the learned resourcefulness levels vary in individuals raised in different environments (Rosenbaum 1983). Such skills developed under the learned resourcefulness are closely related to life stories and experiences of individuals (Erden, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As for the target populations, both measurements were generally developed for assessing the resourcefulness of adults. However, Rosenbaum’s SCS Scale has been used in diverse studies investigating adolescents (Bilgin & Akkapulu, 2007; Bingol & Buzlu, 2016; Erden & Ümmet, 2014; Huang & Guo, 2009; Huang, Sousa, Tu, Hwang, 2005; Turkel & Tezer, 2008) and adult children’s resourcefulness (Akgun & Ciarrochi, 2003; Benedict, Jason, & Katesy, 2008; Ceyhan, 2006; Ceyhan & Ceyhan, 2011; Ginter et al, 1988; Goff, 2011; Kennett, 1994; Kennett & Keefer, 2006; McWhirter, 1997).…”
Section: Discussion On Critical Issuesmentioning
confidence: 99%
“…Parental attitudes also shape how the child will react to stressful life events in his/her future life and what kind of behavioral repertoire he/she will have in these situations. These behavioral repertoires also determine the learned resilience level of the individual in adulthood (Erden & Ümmet, 2014). When the literature is reviewed, it is seen that there are significant relationships between parental attitudes and decision-making styles (Eldeleklioğlu, 1996;Öztürk et al, 2011), decision-making styles and learned resilience (Atsızelti et al, 2017;Deniz, 2004;Ertural, 2019;Salo & Alwood, 2011;Uygur, 2018) and parental attitudes and learned resilience (Coşkun, 2008;Erden & Ümmet, 2014;Hamarta et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These behavioral repertoires also determine the learned resilience level of the individual in adulthood (Erden & Ümmet, 2014). When the literature is reviewed, it is seen that there are significant relationships between parental attitudes and decision-making styles (Eldeleklioğlu, 1996;Öztürk et al, 2011), decision-making styles and learned resilience (Atsızelti et al, 2017;Deniz, 2004;Ertural, 2019;Salo & Alwood, 2011;Uygur, 2018) and parental attitudes and learned resilience (Coşkun, 2008;Erden & Ümmet, 2014;Hamarta et al, 2010). However, it is seen that the studies conducted are not sufficient to examine the variables affecting this structure in terms of indirect relationships because of the fact that decision-making behavior is a complex structure that can be explained by the interaction of many different factors.…”
Section: Introductionmentioning
confidence: 99%